X‐rays effects on cytoskeleton mechanics of healthy and tumor cells. Issue 1 (31st August 2016) - Panzetta, Valeria; De Menna, Marta; Musella, Ida; Pugliese, Mariagabriella; Quarto, Maria; Netti, Paolo A.; Fusco, Sabato
Abstract : Alterations in the cytoskeleton structure are frequently found in several diseases and particularly in cancer cells. It is also through the alterations of the cytoskeleton structure that cancer cells acquire most of their common features such as uncontrolled cell proliferation, cell death evasion, and the gaining of migratory and invasive characteristics. Although radiation therapies currently represent one of the most effective treatments for patients, the effects of X‐irradiation on the cytoskeleton architecture are still poorly understood. In this case we investigated the effects, over time of two different doses of X‐ray irradiation, on cell cytoskeletons of BALB/c3T3 and Sv40‐transformed BALB/c 3T3 cells (SVT2). Biophysical parameters – focal adhesion size, actin bundles organization, and cell mechanical properties – were measured before and after irradiations (1 and 2 Gy) at 24 and 72 h, comparing the cytoskeleton properties of normal and transformed cells. The differences, before and after X‐irradiation, were revealed in terms of cell morphology and deformability. Finally, such parameters were correlated to the alterations of cytoskeleton dynamics by evaluating cell adhesion at the level of focal adhesion and cytoskeleton mechanics. X‐irradiation modifies the structure and the activity of cell cytoskeleton in a dose‐dependent manner. For transformed cells, radiation sensitively increased cell adhesion, as indicated by paxillin‐rich focal adhesion, flat morphology, a well‐organized actin cytoskeleton, and intracellular mechanics. On the other hand, for normal fibroblasts IR had negligible effects on cytoskeletal and adhesive protein organization. © 2016 Wiley Periodicals, Inc.